改革二十年经济制度变迁对中国区域经济增长差异的影响 = Impacts of institutional and structural changes on China's regional growth disparity - 李胜茹 Li, Shengru (2008)
Six veariables: signaficance of state-owned sector, degree of openness, degree of marketization/government intervention, resource allocation between central and local government, growth of fixed assets investment, and catch-up effect for less developed provinces are identified.